(untitled) (Research, Society and Development, 2023)
Female empowerment and recognition of the role of women and their rights are of paramount importance for global development and human rights, a fact consolidated with the Sustainable Development Goal. Academic leagues are important teaching, research and extension tools within graduation, and enable the improvement of student autonomy. This article aims to report the experience of an academic women’s health league in health promotion, with a focus on women’s health and women’s empowerment. This is a descriptive study of the experience report type about an academic league focused on women’s health and women’s empowerment and health promotion, through the production of informative/educational content distributed on digital platforms and the provision of scientific events . Academic leagues are of paramount importance for training based on the tripod teaching, research and extension. Offering refresher courses and national congresses is a way to promote dialogue and exchange of knowledge about women’s health between health professionals and students in order to bring evidence-based information to health professionals. In this way, we consider social media to be a highly relevant tool for promoting women’s health, ensuring a greater reach of information for society with regard to women’s health and empowerment. The construction of knowledge must be improved prioritizing social diversity.